Head-Mounted Display-Based Virtual Reality and Physiological Computing for Stroke Rehabilitation: A Systematic Review - Amini Gougeh, Reza; Falk, Tiago H. (Frontiers in Virtual Reality, 2022)
Virtual reality (VR)-mediated rehabilitation is emerging as a useful tool for stroke survivors to recover motor function. Recent studies are showing that VR coupled with physiological computing (i.e., real-time measurement and analysis of different behavioural and psychophysiological signals) and feedback can lead to (1) more engaged and motivated patients, (2) reproducible treatments that can be performed at the comfort of the patient's home, and (3) development of new proxies of intervention outcomes and success. While such systems have shown great potential for stroke rehabilitation, an extensive review of the literature is still lacking. Here, we aim to fill this gap and conduct a systematic review of the twelve studies that passed the inclusion criteria. A detailed analysis of the papers was conducted along with a quality assessment/risk of bias evaluation of each study. It was found that the quality of the majority of the studies ranked as either good or fair. Study outcomes also showed that VR-based rehabilitation protocols coupled with physiological computing can enhance patient adherence, improve motivation, overall experience, and ultimately, rehabilitation effectiveness and faster recovery times. Limitations of the examined studies are discussed, such as small sample sizes and unbalanced male/female participant ratios, which could limit the generalizability of the obtained findings. Finally, some recommendations for future studies are given.